Phthalocyanine-Modified Electrodes Used in the Electroanalysis of Monoamine Neurotransmitters - Anton Alexandru Ciucu; Mihaela Buleandră; Dana Elena Popa; Dragoș Cristian Ștefănescu (Chemosensors, 2025)
Metallo-phthalocyanines (MPcs) are versatile materials with applications in electroanalysis because of their superior catalytic properties. This review presents the electrochemical methods based on MPc-modified electrodes and reports some of their remarkable properties and applications in the electroanalysis of monoamine neurotransmitters and biomolecules that play a crucial role in vital functions of the human body. The development of electrocatalytic chemically modified electrodes is based on their ability to provide a selective and rapid response toward a specific analyte in complex media without the need for sample pretreatment. The explanation of several phenomena occurring at the MPc-modified electrode surface (e.g., MPc-mediated electrocatalysis), the advantages of promoting different electron transfer reactions, and the detection mechanism are also presented. The types of MPcs and different materials, such as carbon nanotubes and graphene, used as substrates for modified working electrodes are discussed. Modifying the properties of MPcs through various interactions, or combining MPcs with carbonaceous materials, creates a synergistic effect. Such hybrid materials present both extraordinary catalytic and increased conductivity properties. We conducted a compilation study based on recent works to demonstrate the efficacy of the developed sensors and methods in sensing monoamine neurotransmitters. We emphasize the analyte type, optimized experimental parameters, working range, limits of detection and quantification, and application to real samples. MPc–carbon hybrids have led to the development of sensors with superior sensitivity and improved selectivity, enabling the detection of analytes at lower concentrations. We highlight the main advantages and drawbacks of the discussed methods. This review summarizes recent progress in the development and application of metallo-phthalocyanine-modified electrodes in the electroanalysis of monoamine neurotransmitters. Some possible future trends are highlighted.